Ultrasound signs of atherosclerotic plaques destabilization in carotid arteries - D. E. Zaitsev; A. S. Lepekhina; G. E. Trufanov (Российский кардиологический журнал, 2019)
Aim. To assess the ultrasonography role for diagnosis of atherosclerotic lesions of the extracranial carotid arteries.Material and methods. The study was conducted on the basis of the St. Petersburg Mariinsky Hospital. A total of 855 patients who were admitted to the regional vascular center due to ischemic stroke or transient ischemic attack were examined. The mean age of the patients was 68 years (min 18, max 107). All patients underwent ultrasound of the carotid arteries.Results. In 570 (66,6%) patients with neurological symptoms (according to clinical and neurological examination), hemodynamically insignificant carotid artery lumen stenosis up to 70-75% was revealed. Ultrasound imaging in all patients revealed signs of atherosclerotic plaque (ASP) instability in various combinations, except for hemorrhage. It was not possible to clearly visualize the finished hemorrhage in the ASP structure.Conclusion. Despite the high informative value of ultrasound, it is not possible to answer all clinical questions with its single use. At the moment, there is no classification of instability signs, reflecting the ASP embolism risk. It needs for paternal change the management of asymptomatic patients. More detailed study of ASP destabilization using various visualization methods is necessary.